2008
DOI: 10.1021/ja806345q
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solvent, pH, and Molecular Size in Excited-State Deactivation of Key Eumelanin Building Blocks: Implications for Melanin Pigment Photostability

Abstract: Ultrafast time-resolved fluorescence spectroscopy has been used to investigate the excited-state dynamics of the basic eumelanin building block 5,6-dihydroxyindole-2-carboxylic acid (DHICA), its acetylated, methylated, and carboxylic ester derivatives, and two oligomers, a dimer and a trimer in the O-acetylated forms. The results show that (1) excited-state decays are faster for the trimer relative to the monomer; (2) for parent DHICA, excited-state lifetimes are much shorter in aqueous acidic medium (380 ps) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
114
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 43 publications
7
114
1
1
Order By: Relevance
“…The fact that the red-shifted (>420 nm) fluorescence characteristic of the zwitterionic species is observed also for the dimers ( Figures 4B and SI3A) is direct evidence for the COOH → NH process. 18,20,30 FU now shows that ESIPT occurs with an ∼190 fs time constant in fully protonated DHICA dimers (see more below), and streak camera measurements ( Figure 4B) show that the zwitterionic proton transfer product decays with an ∼140 ps time constant, somewhat faster than the corresponding monomer decay.…”
Section: ■ Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The fact that the red-shifted (>420 nm) fluorescence characteristic of the zwitterionic species is observed also for the dimers ( Figures 4B and SI3A) is direct evidence for the COOH → NH process. 18,20,30 FU now shows that ESIPT occurs with an ∼190 fs time constant in fully protonated DHICA dimers (see more below), and streak camera measurements ( Figure 4B) show that the zwitterionic proton transfer product decays with an ∼140 ps time constant, somewhat faster than the corresponding monomer decay.…”
Section: ■ Discussionmentioning
confidence: 70%
“…We previously showed that a solvent controlled ESIPT is responsible for the ultrafast (∼300 fs) excited state decay of the (protonated, pH 2.5) neutral DHICA monomer and formation of a zwitterionic state with short-lived, ∼240 ps, and red-shifted emission. 18,20,30 With this in mind, it could be expected that also the fully protonated (pH 2.5) dimers (and oligomers) exhibit very fast ESIPT and excited state decay as is in fact demonstrated by the ∼190 fs fluorescence decay (Figure 4). The fact that the red-shifted (>420 nm) fluorescence characteristic of the zwitterionic species is observed also for the dimers ( Figures 4B and SI3A) is direct evidence for the COOH → NH process.…”
Section: ■ Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As described above, at low pH (e.g., pH 2.5), the fluorescence band observed at 450 nm is due to a zwitterionic species suggested to be formed through an unresolved subpicosecond ESIPT process 6,11 involving the COOH and NH groups of DHICA. Figure 2 shows the FU decay of the originally excited molecule measured at 380 nm.…”
mentioning
confidence: 75%
“…At the same time, solvent (water) molecules were shown to play an important role in the proton transfer, 13 implying that the exact nature of interaction between the proton dissociated from the COOH group and the NH group has still to be established. At high pH (11), when the molecule is doubly deprotonated, a red-shifted fluorescence peaking at ∼416 nm is observed, which we consequently attribute (mainly) to the DHICA 2− species. The measured fluorescence spectra at intermediate pH values are a result of coexisting species.…”
mentioning
confidence: 76%